O Modus Vivendi entre Moçambique e o Transvaal (1901-1909): Um caso de «imperialismo ferroviário» - Bouene, Felizardo; Santos, Maciel (Africana Studia, 2020)
Since the opening of the Transvaal mines, the complex connections between the Portuguese colony of Mozambique and the South-African territories were considered crucial to the Anglo-Portuguese political agenda. Bilateral negotiations about the railway line, from the “natural port” of the mines to its hinterland, quickly left the colonial level of Cape Town and Lourenço Marques to become a metropolitan diplomatic issue. Access to labour recruitment in Mozambique and railway differentials were the main items in the renewal of the 1901 agreement, the Modus Vivendi, which would only be signed in 1909. Comparing the Foreign Office papers and the Portuguese official reports helps us to understand one of the most determinant processes of the new economic geography of Southern Africa.